ANALISIS HUBUNGAN MOTIVASI BELAJAR TERHADAP PRESTASI AKADEMIK SISWA SMP DARUL AKHLAQ - Arif Hidayat; Irma Mila Karimah; Devy Habibi Muhammad; Agatha Lola Margareta Margareta; Nurul Hidayah (Fakultas Agama Islam Universitas Billfath, 2025)
This study aims to examine the relationship between learning motivation—both intrinsic and extrinsic—and academic achievement among students at SMP Darul Akhlaq, Probolinggo Regency. The research employed a quantitative correlational approach involving 34 students from three grade levels in the 2024/2025 academic year. Data were collected through a Likert-scale questionnaire and academic report documentation, then analyzed using SPSS 24. Validity testing confirmed that all questionnaire items were valid, and the reliability test yielded a Cronbach’s Alpha value of 0.581, indicating acceptable reliability. Simple linear regression analysis showed an R value of 0.717 and R² of 0.514, indicating that learning motivation contributes 51.4% to variations in students’ academic achievement. These findings underscore the significant role of motivation in academic success and highlight the need for school-based interventions to create a supportive learning environment. This study offers contextual contributions by focusing on an Islamic school setting, which remains underexplored in research on this topic.